TIM3 Expression in Anaplastic-Thyroid-Cancer-Infiltrating Macrophages: An Emerging Immunotherapeutic Target - Palacios, Luz María (2022)
Anaplastic thyroid cancer (ATC) is a clinically aggressive form of undifferentiated thyroid cancer with limited treatment options. Immunotherapy for patients with ATC remains challenging. Tumor-associated macrophages (TAMs) constitute over 50% of ATC-infiltrating cells, and their presence is associated with a poor prognosis. Consequently, the development of new therapies targeting immune checkpoints in TAMs is considered a promising therapeutic approach for ATC. We have previously shown that soluble factors secreted by ATC cells induced pro-tumor M2-like polarization of human monocytes by upregulating the levels of the inhibitory receptor TIM3. Here, we extended our observations on ATC-cell-induced xenograft tumors. We observed a large number of immune cells infiltrating the ATC xenograft tumors. Significantly, 24–28% of CD45+ immune cells were macrophages (CD11b+ F4/80+). We further showed that 40% of macrophages were polarized toward a M2-like phenotype, as assessed by CD206 expression and by a significant increase in the Arg1/iNOS (M2/M1) ratio. Additionally, we found that ATC xenograft tumors had levels of TIM3 expression when determined by RT-PCR and immunofluorescence assays. Interestingly, we detected the expression of TIM3 in macrophages in ATC tumors by flow cytometry assays. Furthermore, TIM3 expression correlated with macrophage marker expression in human ATC. Our studies show that TIM3 is a newly identified immune checkpoint in macrophages. Since TIM3 is known as a negative immune regulator, it should be considered as a promising immunotherapeutic target for ATC.